2020
DOI: 10.15406/jabb.2020.07.00222
|View full text |Cite
|
Sign up to set email alerts
|

A review on lignin sources and uses

Abstract: The efficient use of renewable resources has become a driving force for the worldwide industry aiming to improve the competitiveness. Considering the available natural raw materials, the lignin present in the lignocellulosic biomass such as trees, is the unique natural polymer that presents aromatic rings in its constitution. In this way, this review details the structure of native lignin as well as the technical lignin, including information on the characteristics that this polymer must have for the most prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(56 reference statements)
0
24
0
2
Order By: Relevance
“…Technical lignin is obtained as a by-product of several separation processes that most lignocellulosic materials undergo for some of their transformation processes. The composition and characteristics of technical lignin may vary according to the type and characteristics of the separation process, so, in order to assess the usefulness of the obtained lignin for use in other processes, each technical lignin batch must be considered [ 56 ].…”
Section: Bio-based Wood Adhesivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical lignin is obtained as a by-product of several separation processes that most lignocellulosic materials undergo for some of their transformation processes. The composition and characteristics of technical lignin may vary according to the type and characteristics of the separation process, so, in order to assess the usefulness of the obtained lignin for use in other processes, each technical lignin batch must be considered [ 56 ].…”
Section: Bio-based Wood Adhesivesmentioning
confidence: 99%
“…The kraft process implies mixing alkaline chemicals such as NaOH and sodium sulphide (Na 2 S) with lignocellulosic materials and then introducing high temperatures, from 140 to 170 °C, obtaining what is commonly referred to as black liquor, containing degraded lignin, oxidised inorganic compounds, and other organic materials. In order to separate the kraft lignin from the black liquor, it is required to undergo an acidification process [ 56 ]. The resulting lignin may have impurities such as sulphur, which must be carefully considered when assessing its potential uses.…”
Section: Bio-based Wood Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that we must find a renewable resource to replace petroleum-based raw materials for the production of energy and chemicals. Lignin is one of the three main components of biomass and is the most abundant natural source of aromatic polymers and has attracted attention in this respect [ 1 , 2 ]. The most abundant source of lignin is currently from kraft pulping, which is used in almost 90% of the world’s pulp production [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their oxidative enzymatic polymerization leads to the phydroxyphenyl, guaiacyl, and sinapyl units found in lignin structure (Ralph et al 2004). The current trends have shown that lignin may be a good alternative for feedstock of phenol-derived products, even the replacement of petrochemical-derived aromatic monomers, technical carbons, fuels, and adhesives (De Souza et al 2020). Nevertheless, technical lignins' physico-chemical properties highly depend on their extraction process (solubility, sulfur content, molecular weight for instance), and on the original feedstock (Watkins et al 2015).…”
Section: Introductionmentioning
confidence: 99%